2010
DOI: 10.1124/mol.110.065961
|View full text |Cite
|
Sign up to set email alerts
|

Amurensin G, a Potent Natural SIRT1 Inhibitor, Rescues Doxorubicin Responsiveness via Down-Regulation of Multidrug Resistance 1

Abstract: The transition from a chemotherapy-responsive cancer to a chemotherapy-resistant one is accompanied by increased expression of multidrug resistance 1 (MDR1, p-glycoprotein), which plays an important role in the efflux from the target cell of many anticancer agents. We recently showed that a Forkhead box-containing protein of the O subfamily 1 (FoxO1) is a key regulator of MDR1 gene transcription. Because nuclear localization of FoxO1 is regulated by silent information regulator two ortholog 1 (SIRT1) deacetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 38 publications
(52 reference statements)
3
53
0
4
Order By: Relevance
“…We have previously shown that phosphorylated FOXO1 is overexpressed in gastric cancer specimens and that FOXO1 inactivation is related to better prognosis of gastric cancer patients [18]. Although FOXO proteins, especially FOXO1 and FOXO3, have been reported to be related to chemoresistance in various cancer cells [8][9][10][19][20][21], their involvement in chemoresistance of gastric cancer cells has not been reported. In the present study, we used two gastric cancer cell lines, MKN45 and SNU-601, with constitutive FOXO1 expression and found that CDDP treatment increased the levels of FOXO1 protein expression and activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that phosphorylated FOXO1 is overexpressed in gastric cancer specimens and that FOXO1 inactivation is related to better prognosis of gastric cancer patients [18]. Although FOXO proteins, especially FOXO1 and FOXO3, have been reported to be related to chemoresistance in various cancer cells [8][9][10][19][20][21], their involvement in chemoresistance of gastric cancer cells has not been reported. In the present study, we used two gastric cancer cell lines, MKN45 and SNU-601, with constitutive FOXO1 expression and found that CDDP treatment increased the levels of FOXO1 protein expression and activation.…”
Section: Discussionmentioning
confidence: 99%
“…The function of FOXO1 in chemoresistance in cancer cells has been evaluated in in vitro studies [8][9][10]. FOXO1 increased doxorubicin resistance in breast cancer cells [8] and paclitaxel resistance in ovarian cancer cells [9], whereas it decreased CDDP resistance in ovarian cancer cells [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer cells, FOXO1 downregulation is associated with cancer progression and resistance to chemotherapy [5][6][7], and its function is inhibited by the phosphatidylinositol 3-kinase-Akt-FOXO1 axis [8]. Therefore, the FOXO1 regulating mechanism has been speculated to be a promising target to overcome refractory GC.…”
Section: Introductionmentioning
confidence: 99%
“…Researches find that, multidrug resistance (MDR) is the most important cellular defense mechanism for malignant tumor to drug attack (Oh et al, 2010), and an important reason for treatment failure and tumor recurrence and metastasis, which is a problem urgent to be solved in clinic. It is cross-resistance phenomenon of tumor cells to a variety of unrelated drugs with different molecular structures, cellular targets and action mechanisms.…”
Section: Bcrp Expression In Vx2 Rabbit Liver Tumours and Its Effects mentioning
confidence: 99%